Unlocking the origins and biology of domestic animals using ancient DNA and paleogenomics - McHugo, Gillian P. (BMC Biol, 2019)
Animal domestication has fascinated biologists since Charles Darwin first drew the parallel between evolution via natural selection and human-mediated breeding of livestock and companion animals. In this review we show how studies of ancient DNA from domestic animals and their wild progenitors and congeners have shed new light on the genetic origins of domesticates, and on the process of domestication itself. High-resolution paleogenomic data sets now provide unprecedented opportunities to explore the development of animal agriculture across the world. In addition, functional population genomics studies of domestic and wild animals can deliver comparative information useful for understanding recent human evolution.